Resorption of roots of different dimension induced by different types of forces - Cuoghi, Osmar Aparecido [UNESP]; Aiello, Carlos Alberto; Consolaro, Alberto; Tondelli, Pedro Marcelo; Mendonça, Marcos Rogério de [UNESP] (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2014)
Root resorption is a variable to be considered in induced tooth movement (ITM). It is related to root morphology and alveolar bone crest, and also to the types of forces exerted by mechanotherapy. This histometric study evaluated the predominance of root resorption among roots of different dimensions, following ITM with different types of forces and at different time intervals. The study was conducted on 54 rats divided into three groups, according to the type of force: continuous (CF), continuous interrupted (CIF) and intermittent (IF), at periods of 5, 7 and 9 days. The percentage of resorption between mesiobuccal roots of larger dimension and intermediate roots of smaller dimension was assessed. The evaluations were performed on the AxioVision software, and the non-parametric analysis of variance for repeated measures in independent groups was further applied, consisting of a scheme of two factors, and complemented by the Dunn test at a significance level of 5%. The intermediate roots presented a higher percentage of resorption, which was gradual at the periods evaluated for the three types of forces, but mainly for CF. Comparing the intermediate roots with the mesiobuccal roots, there was a statistically significant difference (p < 0.05) in the CF group at day 7 and day 9, and in the FI group, at day 9. The intragroup analysis evidenced a statistically significant difference (p < 0.05) between the 5th and the 9th day for the intermediate root in the CF group. The intergroup analysis did not reveal any statistically significant difference (p > 0.05) in individually analyzed roots.
Keywords: Root Resorption; Tooth Movement; Rats